A Comparative Study of the Latest Editions of China–Japan–US Green Building Evaluation Standards - Qiyuan Wang; Weijun Gao; Yuan Su; Yinqi Zhang (Buildings)
The Green Building Evaluation Standard (ESGB) has become an important support for China’s building sector in realizing the “double carbon” goal. However, there remains a lack of comprehensive research on the historical evolution and development status of the ESGB. This study firstly analyzes the updating logic and development strategy of the three versions of the ESGB, then compares the differences between ESGB 2019, CASBEE-NC 2014, and LEED O+M v4.1 from the perspective of the index system, and further examines the current international application status of the ESGB. The results show that LEED focuses on decarbonization and ecological protection, while CASEBB focuses on the concept of humanization and positively influences the local real estate market, and ESGB 2019 contains more health and comfort considerations than its previous version and is close to the internationally advanced level in terms of provision setting and international application. This study offers valuable insights into the potential for further refinement of green building standards in China and highlights areas for future research, including enhancing the ESGB’s adaptability and integration with emerging technologies to promote global sustainable development.